A New Kind of Fuzzy n-ary Hypergroups in the Framework of Soft Set Theory - Hongjie Li; Yunqiang Yin (The Scientific World Journal)
Maji et al. introduced the concept of fuzzy soft sets as a generalization of the standard soft sets and presented an application of fuzzy soft sets in a decision making problem. The aim of this paper is to apply the concept of fuzzy soft sets to n-ary hypergroup theory. The concepts of (∈γ,∈γ∨qδ)-fuzzy soft (invertible) n-ary subhypergroups over a commutative n-ary hypergroup are introduced and some related properties and characterizations are obtained. The homomorphism properties of (∈γ,∈γ∨qδ)-fuzzy soft (invertible) n-ary subhypergroups are also derived.